Pharmacological and genetic inhibition of fatty acid‐binding protein 4 alleviated cisplatin‐induced acute kidney injury. Issue 9 (8th July 2019) - Tan, Zhouke; Guo, Fan; Huang, Zhuo; Xia, Zijing; Liu, Jing; Tao, Sibei; Li, Lingzhi; Feng, Yuying; Du, Xiaoyan; Ma, Liang; Fu, Ping
Abstract: Fatty acid‐binding protein 4 (FABP4) has been confirmed to be involved in the pathogenesis of ischaemia/reperfusion‐ and rhabdomyolysis‐induced acute kidney injury (AKI), and targeting inhibition of FABP4 might be a potential strategy for AKI. Cisplatin as a commonly used cancer chemotherapeutic drug possessed a dose‐limited side effect of nephrotoxicity. However, whether FABP4 inhibition exerted a favourable renoprotection against cisplatin‐induced AKI and the involved mechanisms remained unknown. In the study, cisplatin‐injected mice developed severe AKI symptom as indicated by renal dysfunction and pathological changes, companied by the high expression of FABP4 in tubular epithelial cells. Selective inhibition of FABP4 by BMS309403 at 40 mg/kg/d for 3 days and genetic knockout of FABP4 significantly attenuated the serum creatinine, blood urea nitrogen level and renal tubular damage. Mechanistically, cisplatin injection induced the increased apoptosis and regulated the corresponding protein expression of BCL‐2, BCL‐XL, BAX, cleaved caspase 3 and caspase 12 in the injured kidney tissues. Cisplatin also triggered multiple signal mediators of endoplasmic reticulum (ER) stress including double‐stranded RNA‐activated protein kinase‐like ER kinase, activating transcription factor‐6 and inositol‐requiring enzyme‐1 pathway, as well as CHOP, GRP78 and p‐JNK proteins in the kidneys. Oral administration of BMS309403 significantly reduced the number of renal TUNEL‐positive apoptotic cells. Knockout of FABP4 and BMS309403 notably improved ER stress‐related apoptotic responses. In summary, pharmacological and genetic inhibition of FABP4 modulated apoptosis via the inactivation of ER stress in the tubular epithelial cells of cisplatin‐induced AKI.